2003
DOI: 10.1667/rr3042
|View full text |Cite
|
Sign up to set email alerts
|

No Lengthening of Life Span in Mice Continuously Exposed to Gamma Rays at Very Low Dose Rates

Abstract: Late effects of continuous exposure to ionizing radiation are potential hazards to workers in radiation facilities as well as to the general public. Recently, low-dose-rate and low-dose effects have become a serious concern. Using a total of 4000 mice, we studied the late biological effects of chronic exposure to low-dose-rate radiation as assayed by life span. Two thousand male and 2000 female 8-week-old specific-pathogen-free (SPF) B6C3F1 mice were randomly divided into four groups (one nonirradiated control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 24 publications
6
38
0
Order By: Relevance
“…Similar studies on mice irradiated with 414 mGy at a dose rate of 0.86 mGy/d (0.65 µGy/min) showed no detectable change. These characteristics correspond roughly to that observed for life-shortening (Tanaka, Tanaka, Sasagawa, Ichinohe, Takabatake, Matsushita, et al, 2003) and cancer-induction (Tanaka, Tanaka, Ichinohe, Matsushita, Matsumoto, Otsu, et al, 2007), suggesting a role of genomic alteration in radiation-induced cancer and/or life shortening.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar studies on mice irradiated with 414 mGy at a dose rate of 0.86 mGy/d (0.65 µGy/min) showed no detectable change. These characteristics correspond roughly to that observed for life-shortening (Tanaka, Tanaka, Sasagawa, Ichinohe, Takabatake, Matsushita, et al, 2003) and cancer-induction (Tanaka, Tanaka, Ichinohe, Matsushita, Matsumoto, Otsu, et al, 2007), suggesting a role of genomic alteration in radiation-induced cancer and/or life shortening.…”
Section: Resultssupporting
confidence: 80%
“…These dose responses look similar to the effects on life shortening and cancer induction elucidated before under comparable conditions in B6C3 F1 mice (Tanaka, Tanaka, Sasagawa, Ichinohe, Takabatake, Matsushita, et al, 2003;Tanaka, Tanaka, Ichinohe, Matsushita, Matsumoto, Otsu, et al, 2007). It suggests a possible association between genomic alteration and life shortening and/or cancer induction.…”
Section: Data Science Journal Volume 8 24 September 2009supporting
confidence: 85%
“…Although some research groups have recently reported the effects of low doses of radiation on longevity and senescence (17,32,33), the underlying molecular mechanisms remained unknown. We thus focused on the mechanisms by which low doses of ionizing radiation inhibit cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…When the average t x was longer than about 1 day, no tumors appeared and no life shortening was observed. On the other hand, a recent life-span study on specific-pathogen-free B6C3F1 mice used chronic exposure to 137 Cs γ -radiation at 0.05, 1.1, and 21 mGy per day beginning at 8 weeks for 400 days (Tanaka et al, 2003). No lengthening of life span was found.…”
Section: Microdoses At Low Dose Ratementioning
confidence: 98%